The (Slow) Tragedy of Improvement: Neoliberalism, Fisheries Management & the Institutional Commons. (August 2019) - Bresnihan, Patrick
Highlights: Empirical and theoretical contribution to debates on the relationships between neoliberalism, fisheries management, and the institutionalization of the commons. Uses the analytic framework of governmentality to identify important shifts within fisheries management, as demonstrated through the institutional approach to the commons. Demonstrates how efforts to implement community-based management in the Irish lobster fisheries represents continuity and discontinuity with the long tradition of liberal thought and biopolitical "improvement". Develops the concept of "improvement" for analyzing dynamic process of neoliberal fisheries management (and environmental governance more broadly). Argues for greater criticality when it comes to affirming the benefits of the commons as an alternative to dominant forms of economic production and decision-making. Summary: This paper contributes theoretically and empirically to debates on the relationship between neoliberalism and the institutionalization of the commons through an analysis of recent efforts to implement community-managed lobster fisheries in Ireland. This initiative has been influenced by international examples of co-management systems in small-scale, inshore fisheries, and is presented as a "third way" for resource management, moving beyond the limited management choice of privatization or centralized state control. The paper is based on interviews and fieldwork with the fisheries managers, scientists, and inshore fishermen involved in the development of the co-management plan. In the paper, I use the analytic framework of governmentality to examine how these efforts to institutionalize the fisheries commons represent both continuity and discontinuity with the long tradition of liberal thought and biopolitical "improvement". I argue that the continuity stems from the initial formulation of the problem of overfishing as one of unregulated exploitation of a resource; the novelty lies in the critique of existing institutional models, namely privatization and state regulation, that fail to adequately reflect and enable the capacities of local communities to self-manage the resources they exploit. Understanding neoliberal governmentality in terms of "improvement" helps us to understand and take more seriously the rationale behind efforts to devise better institutional responses to the problem of overfishing. The concept of "improvement" helps to broaden the analysis of neoliberalism beyond an often narrowly defined focus on market mechanisms and profit incentives; it shifts the focus of analysis away from the regulatory moments of "enclosure" to the ongoing, often frustrated efforts to align fishers' economic interests with the "long-term" common good. The article argues for a more ambivalent reading of the commons that places greater focus on how localized, collective action can be valued and incorporated within evolving governmental and economic arrangements.